2019
DOI: 10.1017/cts.2019.185
|View full text |Cite
|
Sign up to set email alerts
|

3310 A Community-Academic Partnership to Understand the Association Among Health Status and Senior Services Utilization to Improve Nutrition and Blood Pressure Control for Low Income Seniors Aging in Place

Abstract: OBJECTIVES/SPECIFIC AIMS: The Rockefeller University Center for Clinical and Translational Science (RU-CCTS), Clinical Directors Network (CDN), and Carter Burden Network (CBN), a multi-site senior services organization serving East Harlem, NY, formed a community-academic research partnership to characterize the health of the CBN seniors (many who are racial/ethnic minorities, low-income, and suffering from multiple chronic conditions) and to explore the use and associations of a measure of overall health statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In 2016, The Rockefeller University Center for Clinical and Translational Science (RU) and Clinical Directors Network (CDN), a primary care practice-based research network (PBRN), engaged in a community-academic research partnership with CBN to address unmet health needs among their clients. Incorporating principles of community engagement [ 21 ] and community-based participatory research [ 22 ], a pilot study conducted at two CBN centers found a high prevalence of poorly controlled high blood pressure accompanied by high levels of food insecurity [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, The Rockefeller University Center for Clinical and Translational Science (RU) and Clinical Directors Network (CDN), a primary care practice-based research network (PBRN), engaged in a community-academic research partnership with CBN to address unmet health needs among their clients. Incorporating principles of community engagement [ 21 ] and community-based participatory research [ 22 ], a pilot study conducted at two CBN centers found a high prevalence of poorly controlled high blood pressure accompanied by high levels of food insecurity [ 23 ].…”
Section: Introductionmentioning
confidence: 99%